The State of Cellular Immunity in Children with Infectious Mononucleosis (Texas Journal of Medical Science, 2022)
The main feature of infectious mononucleosis in children is the defeat of the immune system, primarily the T-cell link. Undoubtedly, the low number of CD4 + lymphocytes is associated with reduced resistance to secondary infections. This requires an inadequate immunological response and leads to the chronicity of infectious processes.